MINIMALISASI POTENSI RISIKO STRATEGIS PADA MERGER BANK UMUM SYARIAH ANTARA BANK SYARIAH MANDIRI (BSM), BANK NEGARA INDONESIA SYARIAH (BNIS), DAN BANK RAKYAT INDONESIA SYARIAH (BRIS) - Tubagus Rifqy Thantawi; Miftakhul Anwar; Azizah Mursyidah; Abdul Khoiri; Taufik Hidayatullah (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
Strategic risk is the risk that occurs as a result of the determination and implementation of the company's strategy that is not quite right so that the company suffers losses. Minimization must be carried out so that the bank's strategy is achieved and does not experience losses, especially for Islamic Commercial Banks that carry out mergers. Mergers or mergers in Islamic Commercial Banks between Bank Syariah Mandiri, BNI Syariah, and BRISyariah certainly have positive and negative impacts, where this strategic risk can have a negative impact on this bank. To minimize this strategic risk, consolidation and careful planning is needed from every part of the bank so that they can unite their minds in the newly formed bank.